2018
DOI: 10.1111/dom.13560
|View full text |Cite
|
Sign up to set email alerts
|

FGF21 decreases food intake and body weight in obese Göttingen minipigs

Abstract: Aims The aim of this study was to assess the effect of FGF21 on food intake, body weight, body composition, glucose homeostasis, bone mineral density (BMD), cortisol and growth hormone (GH) in obese minipigs. The pig is a unique model for studying FGF21 pharmacology as it does not express UCP1, unlike mice and humans. Methods Twelve obese Göttingen minipigs with a mean body weight of 91.6 ± 6.7 kg (mean ± SD) received subcutaneously either vehicle (n = 6) or recombinant human FGF21 (n = 6) once daily for 14 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 51 publications
(115 reference statements)
0
16
0
Order By: Relevance
“…Another gene encoded for Fibroblast Growth Factor 21 (FGF21), and was more than 4-fold higher expressed in the HF animals. Subcutaneously injected FGF21 has been described to decrease food intake to 50% and therefore reduce body weight in minipigs [31]. FGF21 regulates triglyceride metabolism and it is shown that overexpression of FGF21 finally would lead to a decline in lipid accumulation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Another gene encoded for Fibroblast Growth Factor 21 (FGF21), and was more than 4-fold higher expressed in the HF animals. Subcutaneously injected FGF21 has been described to decrease food intake to 50% and therefore reduce body weight in minipigs [31]. FGF21 regulates triglyceride metabolism and it is shown that overexpression of FGF21 finally would lead to a decline in lipid accumulation [32].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma FGF‐21 concentrations were negatively correlated with BMD in the femoral neck in Han Chinese adult population, in human immunodeficiency virus 1 (HIV‐1)‐infected patients, and in radial trabecular bone microarchitecture and strength in women with anorexia nervosa . However, others did not detect bone loss in rhFGF‐21–treated or AAV8‐hAAT‐FGF‐21 genetically engineered high‐fat diet–induced obesity mice, in high‐fat–fed obese monkeys and minipigs; and FGF‐21 knockout mice did not show high bone mass phenotype . An independent positive association between plasma FGF‐21 levels and BMD in 24 healthy young women and in postmenopausal women were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…Using human recombinant E.-coli-derived, i. e., non-glycosylated, FGF21, Xu et al reported a half-life of about 1.5-2 h after intravenous injection into C57BL/6 mice [159]. In other studies, half-lives of 20-30 min (CD-1, Swiss Webster mice, cynomolgus macaques [160,161]) and of 1.2 h (Sprague Dawley rats [162]) were measured with the identical protein, and recently a plasma half-life (T½) of 2h for native FGF21 in lean minipigs has been published [163]. Thus, it can be assumed that human (recombinant) FGF21 has a half-life of less than 2 h, while the in vivo stability of endogenous FGF21 is currently unknown.…”
Section: Stability Of Human Fgf21 In the Bloodmentioning
confidence: 96%